On Global Citizenship James Tully in Dialogue - Tully, James (Bloomsbury Academic, 2014)
On Global Citizenship develops James Tully's distinctive and influential approach to political philosophy, first outlined in his 2008 two-volume work Public Philosophy in a New Key, and applies it to the field of citizenship. The second part of the book contains responses from influential interlocutors including Bonnie Honig and Marc Stears, David Owen and Adam Dunn, Aletta Norval, Antony Laden, and Duncan Bell. These provide a commentary not just on the ideas contained in this volume, but on Tully's approach to political philosophy more generally, thus making the book an ideal first source for academics and students wishing to engage with Tully's work. The volume closes with a response from Tully to his interlocutors.